PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA VILLA SEMANA RESORT & SPA - Ni Wayan Raheni; I Gusti Agung Ngurah Gede Eka Teja Kusuma; I Gede Rihayana (EMAS, 2021)
Human Resource Management is a human processing process, through planning, recruitment, compensation selection, safety and health and maintaining relationships until termination of employment in order to achieve company goals and increase welfare. Performance is important in organizations because performance is considered a measure of manager success. in managing the organization and its human resources. Organizational culture is a cognitive framework consisting of attitudes, values, behavioral norms and expectations that are shared by members of the organization. Medium Compensation is everything that employees receive in return for their work. Compensation programs are also important for companies, because they reflect the organization's efforts to maintain human resources. This study aims to determine the effect of organizational culture and compensation on employee performance. The population in this study were all employees at Villa Semana Resort & Spa, as many as 47 employees. In this study the total population sample was 47 employees. The results of this research on organizational culture. and compensation has a positive and significant effect on employee performance